2013
DOI: 10.1186/1472-6831-13-57
|View full text |Cite
|
Sign up to set email alerts
|

Does orthodontic treatment provide a real functional improvement? a case control study

Abstract: BackgroundElectromyographic analysis of the masticatory muscles provides useful data on the behavior of these muscles during stomatognathic system functioning and allows a functional assessment of orthodontic treatments. This study was undertaken to verify if achieving an Angle Class I bite through orthodontic treatment can lead to neuromuscular balance.MethodsThis study enrolled 30 patients (20 females, 10 males, mean age: 15.78 years) with an Angle Class II, division 1 malocclusion that was orthodontically t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 39 publications
1
27
1
2
Order By: Relevance
“…EMG analysis in this study showed that the potentials of TA were higher than that of MM in all periods. This is consistent with the other studies which investigated the EMG [ 36 , 37 , 38 ]. Wieczorek et al [ 36 ] found that the voltage recorded in TA is higher than that in MM in healthy subjects.…”
Section: Discussionsupporting
confidence: 93%
“…EMG analysis in this study showed that the potentials of TA were higher than that of MM in all periods. This is consistent with the other studies which investigated the EMG [ 36 , 37 , 38 ]. Wieczorek et al [ 36 ] found that the voltage recorded in TA is higher than that in MM in healthy subjects.…”
Section: Discussionsupporting
confidence: 93%
“…Surface Electromyography (sEMG) has become an important complementary method in the search for a more comprehensive evaluation of the muscles of the stomatognathic system, because it captures information about the electrical activity of these muscles. sEMG can assist in determining conducts and demonstrating results obtained by specifically employed treatments, in addition to adding knowledge to studies on different facial and occlusal characteristics (1)(2)(3) .…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have highlighted the importance of electromyographic and kinesiografic analysis in the assessment of Stomatognathic System and mandibular kinematics [ 17 22 ].…”
Section: Introductionmentioning
confidence: 99%